2019
DOI: 10.1111/jcmm.14701
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of long non‐coding RNA LINC00176 suppresses ovarian cancer progression by BCL3‐mediated down‐regulation of ceruloplasmin

Abstract: Ovarian cancer is a common malignancy among women with some clinically approved diagnostic coding gene biomarkers. However, long non‐coding RNAs (lncRNAs) have been indicated to play an important role in controlling tumorigenesis of ovarian cancer. Hereby, the aim of the study was to uncover the function of lncRNA LINC00176 in the development and progression of ovarian cancer by regulating ceruloplasmin (CP). Bioinformatics prediction in combination with RT‐qPCR analysis for the expression pattern of LINC00176… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…These categories are not mutually exclusive. For instance, Linc00176 acts as a scaffold to keep BCL3 and p50 together (NF-κB family) and at the same time recruits this complex to the ceruloplasmin promoter to activate its expression [139]. Some reports of transcriptional regulation by lncRNAs do not fit this classification at all, as in the case of FAL1, which increases the stability of BMI (another subunit of PRC), thereby allowing epigenetic marking of the p21 gene to be silenced [31,42].…”
Section: Transcriptional Regulationmentioning
confidence: 99%
“…These categories are not mutually exclusive. For instance, Linc00176 acts as a scaffold to keep BCL3 and p50 together (NF-κB family) and at the same time recruits this complex to the ceruloplasmin promoter to activate its expression [139]. Some reports of transcriptional regulation by lncRNAs do not fit this classification at all, as in the case of FAL1, which increases the stability of BMI (another subunit of PRC), thereby allowing epigenetic marking of the p21 gene to be silenced [31,42].…”
Section: Transcriptional Regulationmentioning
confidence: 99%
“…For example, lncRNA LINC00176 was highly expressed in OC tissues as well as in OC cell lines, respectively. Knockdown of lncRNA LINC00176 suppresses OC progression by BCL-mediated downregulation of ceruloplasmin [12]. Li et al suggested that lncRNA UCA1 was upregulated in cisplatin-resistant patient tissues and cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…For example, lncRNA LINC00176 was highly expressed in OC tissues as well as in OC cell lines, respectively. Knockdown of lncRNA LINC00176 suppresses OC progression by BCL-mediated downregulation of ceruloplasmin [12]. Li et al suggested that lncRNA UCA1 was upregulated in cisplatinresistant patient tissues and cell lines.…”
Section: Introductionmentioning
confidence: 99%